“Apacin” Learning Model in Writing Poetry for Elementary School - Koeswanti, Henny Dewi (Universitas Pendidikan Ganesha, 2021)
Students have difficulty understanding the learning material, which has an impact on students' low abilities. It will have an impact on low student learning outcomes. Many factors cause students difficulty in understanding the learning material. One of the influencing factors is the learning model. This research aims to produce a new learning model development called APACIN, an acronym for the learning syntax Observe, Think, Analyze, Create, and Information. The method used in this research is descriptive qualitative with a case study approach to elementary school students. The result of this study is that the APACIN learning model can provide alternative solutions to learning problems faced by teachers and students. Through this APACIN learning model, teachers and students can interact more, and students individually and in groups can provide solutions to contextual problems discussed in learning. In addition, the application of the APACIN learning model can build critical thinking, creative thinking, reflective thinking, and decision making in students. The APACIN learning model will make it easier for students to learn so that it will impact increasing student learning outcomes.